DoE-based medium optimization for improved biosurfactant production with Aureobasidium pullulans - Haala, Frederick; Dielentheis-Frenken, Marie R. E.; Brandt, Friedrich M.; Karmainski, Tobias; Blank, Lars M.; Tiso, Till (Frontiers in Bioengineering and Biotechnology, 2024)
Polyol lipids (a.k.a. liamocins) produced by the polyextremotolerant, yeast-like fungus Aureobasidium pullulans are amphiphilic molecules with high potential to serve as biosurfactants. So far, cultivations of A. pullulans have been performed in media with complex components, which complicates further process optimization due to their undefined composition. In this study, we developed and optimized a minimal medium, focusing on biosurfactant production. Firstly, we replaced yeast extract and peptone in the best-performing polyol lipid production medium to date with a vitamin solution, a trace-element solution, and a nitrogen source. We employed a design of experiments approach with a factor screening using a two-level-factorial design, followed by a central composite design. The polyol lipid titer was increased by 56 % to 48 g L -1 , and the space-time yield from 0.13 to 0.20 g L -1 h -1 in microtiter plate cultivations. This was followed by a successful transfer to a 1 L bioreactor, reaching a polyol lipid concentration of 40 g L -1 . The final minimal medium allows the investigation of alternative carbon sources and the metabolic pathways involved, to pinpoint targets for genetic modifications. The results are discussed in the context of the industrial applicability of this robust and versatile fungus.